2007
DOI: 10.1002/jmri.20976
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging for ischemic heart disease

Abstract: Cardiac MRI has long been recognized as an accurate and reliable means of evaluating cardiac anatomy and ventricular function. Considerable progress has been made in the field of cardiac MRI, and cardiac MRI can provide accurate evaluation of myocardial ischemia and infarction (MI). Late gadolinium (Gd)-enhanced MRI can clearly delineate subendocardial infarction, and the assessment of transmural extent of infarction on late enhanced MRI has been shown to be useful in predicting functional recovery of dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 91 publications
0
22
0
1
Order By: Relevance
“…The clinical impact of perfusion CMR as a non-invasive technique for the assessment of ischemic heart disease is rapidly increasing [10]. In children CAD is much less frequent than in adults and mainly related to congenital heart defects and their surgical repair, or to inflammatory disease affecting the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical impact of perfusion CMR as a non-invasive technique for the assessment of ischemic heart disease is rapidly increasing [10]. In children CAD is much less frequent than in adults and mainly related to congenital heart defects and their surgical repair, or to inflammatory disease affecting the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac magnetic resonance imaging (MRI), extracellular contrast agents such as various gadolinium (Gd 3þ ) chelates, are now routinely used in clinical practice, as well as in research protocols to assess myocardial perfusion or interstitial space remodeling (1)(2)(3). Intracellular MR contrast agents can provide additional information on the cellular metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Since myocardial perfusion MRI has a high spatial resolution, it provides more accurate evaluation of myocardial ischemia, allowing detection of subendocardial ischemia in patients with mild-to-moderate CAD (15), as well as detection of diffuse subendocardial ischemia in patients with multivessel disease (balanced ischemia) (16), which might be missed by SPECT. Previous multicenter, multivendor head-to-head comparison trials have suggested that perfusion MRI is a valuable alternative to SPECT for the detection of significant anatomic CAD, with superior diagnostic performance, especially in multivessel disease (17)(18)(19).…”
Section: Assessment Of Myocardial Perfusionmentioning
confidence: 99%